2016
DOI: 10.1002/14651858.cd008605.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine agonists for preventing ovarian hyperstimulation syndrome

Abstract: ⊕⊝⊝⊝ Very low 1,5 *The risk in the intervention group (and its 95% confidence interval) is based on the assumed risk in the comparison group and the relative effect of the intervention (and its 95% CI).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
(6 reference statements)
1
21
0
1
Order By: Relevance
“…Ovarian hyperstimulation syndrome (OHSS) is a disease state that occur secondary to ovarian stimulation in which ovaries were enlarged with fluid transudation into body spaces and subsequent reduction of circulatory volume that may predispose to increased risk of venous thrombosis and decreased organ perfusion [ 1 ]. Multiple predisposing factors were supposed for the possibility of developing OHSS during ovarian stimulation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…Ovarian hyperstimulation syndrome (OHSS) is a disease state that occur secondary to ovarian stimulation in which ovaries were enlarged with fluid transudation into body spaces and subsequent reduction of circulatory volume that may predispose to increased risk of venous thrombosis and decreased organ perfusion [ 1 ]. Multiple predisposing factors were supposed for the possibility of developing OHSS during ovarian stimulation protocols.…”
Section: Introductionmentioning
confidence: 99%
“…However, the initial interest and enthusiasm for IVM has waned, due to the perceived lower pregnancy rates achieved with IVM treatment and the relatively recent introduction of easily accessible strategies to reduce the risk of OHSS. Such modifications in the stimulation protocols for women with PCOS, undergoing IVF treatment perceived to be at a significant risk of OHSS, include the use of GnRH antagonist protocols [ 22 ], with the use of a GnRH agonist as a trigger injection prior to oocyte retrieval, the concurrent use of metformin during stimulation [ 21 , 23 ], and the use of dopamine agonists [ 5 ]. However, despite these strategies, OHSS still occurs, albeit with less frequency [ 3 ].…”
Section: Indications For Ivmmentioning
confidence: 99%
“…However, when undergoing IVF treatment, women with PCOS are predisposed to developing ovarian hyperstimulation syndrome (OHSS) due to their high antral follicle count; this facet also make them ideal for in vitro maturation (IVM) treatment [ 3 , 4 ]. OHSS is a significant cause of discomfort, distress, hospitalisation, and even mortality for women undergoing IVF treatment, due to the extravasation of fluid out of the vascular system leading to the development of ascites and potentially pleural effusion and thromboembolic phenomena [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bromocriptine, one of the dopamine receptor agonists (DA) (5,14,15),which inhibits the vascular permeability by blocking VEGF-receptor binding pathways has been found to reduce the angiogenic factors releasing and the vascular permeability for OHSS prevention by inhibiting VEGF receptors' phosphorylation (16)(17)(18)(19)(20). Some studies showed that vaginal administration of bromocriptine could reduce the probability of adverse reactions in the digestive tract and nervous system, and has a preventive effect on OHSS (15). Bromocriptine as dopamine receptor agonists is currently often used for the OHSS prevention (21).…”
Section: Introductionmentioning
confidence: 99%